Client data backup screen saver (in collaboration with backup server) / Wahida Zakaria - Zakaria, Wahida (2005)
On this project paper, I am focusing on the client side. This project paper involves client and server side. Nowadays, tiiere are thousands of people reporting for laptops or notebooks lost and damaged. There could be hundred ways of laptop damaged. One factor that could cause damaged to the laptop is because peoples can bring it anywhere. Therefore it is more vulnerable to accidental damaged and theft. We could put ourselves in danger or risky situation if we have important data stored in the laptop. We should backup the data to any backup media or server. In this project, we recommend clients to use backup software which can be stored in the server rather than storing the data on the same hard disk. Basically, this project is an enhancement of an open source screen saver program and backup program. On my side, I have to create the interface for screen saver setting and enhance it by adding "backup setting" function which will link the screen saver and client program. We also have to modify the program between client and server so that client can send file and server can receive the file and store it. When tlie link between client and server is established and the screen saver cuts in, the selected file will be sent to the server for backup.